Strong Convergence Theorem for Two Commutative Asymptotically Nonexpansive Mappings in Hilbert Space - Jianjun Liu; Lili He; Lei Deng (International Journal of Mathematics and Mathematical Sciences)
C is a bounded closed convex subset of a Hilbert space H, T and S:C→C are two asymptotically nonexpansive mappings such that ST=TS. We establish a strong convergence theorem for S and T in Hilbert space by hybrid method. The results generalize and unify many corresponding results.